Kajian Normatif terhadap Sanksi Administratif Atas Pelanggaran Tata Tertib Narapidana di Lembaga Pemasyarakatan Kelas I Medan - Jacko Valentino Gea; Suhaila Zulkifli (Wajah Hukum, 2026)
The Penitentiary serves as an institution responsible for inmate guidance and security, thus requiring the implementation of internal regulations as a means of maintaining order. The overcrowding condition in Medan Class I Penitentiary increases the potential for disciplinary violations and the need for structured administrative enforcement. This study aims to describe the regulation of inmate conduct, the legal consequences arising from disciplinary violations, and the implementation of administrative sanctions within the institution. The research applies a normative juridical method by reviewing statutory regulations and secondary legal materials, analyzed qualitatively through a descriptive approach. The results indicate that inmate disciplinary rules are regulated systematically under existing legal provisions and violations lead to administrative sanctions such as warnings, restriction of rights, solitary confinement, and disciplinary registers which affect the inmate's eligibility for remission and reintegration rights. The application of administrative sanctions in Medan Class I Penitentiary is carried out through procedural examination by the Penitentiary Observer Team and generally complies with legal standards despite being influenced by overcrowding conditions. The study concludes that administrative sanctions function as instruments of rehabilitation and behavioural control to ensure the security and stability of the penitentiary.